PRILOG RASPRAVI O KAZNI DOŽIVOTNOG ZATVORA I MEĐUNARODNIM PRAVNIM STANDARDIMA - Dragan Jocić (Revija za kriminologiju i krivično pravo)
The latest amendments to the Criminal Code of the Republic of Serbia have quite a lot of controversy among the professional public. The subject of this paper is a critical review of various propositions for overcoming legislative omissions in relation to the sentence of life imprisonment without conditional release for certain criminal offences. Furthermore, this paper deals with prison sentences for crimes for which the conditional release is legally excluded. The intention is to encourage the professional public to find the best solutions for overcoming legally untenable prohibition of conditional release for people sentenced to life imprisonment. The author estimates that pardon, in our legislation, does not represent an effective legal remedy, nor an alternative to conditional release.